Quizizz Assisted Teaching Modules: Mathematics Problem Solving Abilities for Elementary School Students - Royadi Royadi; Aryo Andri Nugroho; Ida Dwijayanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
Students are less accustomed to working on problem-solving questions; this lack of familiarity affects their ability to solve problem-solving questions that are presented after routine questions. In addition, there has been no development of teaching modules carried out by teachers. Therefore, the purpose of this study is to develop a teaching module assisted by Quizizz to improve the ability to solve elementary school mathematics problems that are valid, practical, and effective. This type of research includes development using the ADDIE model design. The data collection methods used are teaching module validation sheets, response questionnaires, and problem-solving questions. The study's findings revealed that the validity of the instructional material, with an average value of 95.69, falls inside the